Clinical InvestigationsBenefits of a dual sagittal crystal transducer for ultrasound imaging during I-125 seed implantation for permanent prostate brachytherapy - Kaljouw, Emmie; Pieters, Bradley; Koedooder, Kees; Lucas, Cees; Koning, Caro (Journal of Contemporary Brachytherapy, 2012)
Purpose : To investigate whether a longer sagittal view and less movement using a dual sagittal crystal probe (DSCP) for trans rectal ultra sound (TRUS) allow for more accurate online-planning in I-125 permanent implant brachytherapy of the prostate, compared to a single sagittal crystal probe (SSCP). Material and methods: Between March 2008 and March 2010, 50 patients with prostate cancer were consecutively included in the study. The first 25 of these patients had both their pre- and online-planning based on a single sagittal crystal probe (SSCP). The treatment-plans of the other 25 patients were based on a DSCP TRUS. Three weeks after implantation a post-planning was made based on CT. TRUS online and CT post-plan dose-volume histogram (DVH) parameters, D 90 and V 100 , were compared for both groups. Also, the post-plan DVH parameters of SSCP were compared to DSCP. The possible factors that might influence the post-plan D 90 and V 100 were analysed using Analysis of Variance (ANOVA). Results: SSCP and DSCP online mean D 90 and V 100 were significantly larger than post-plan mean D 90 and V100 (P < 0.01). The post-plan mean D 90 and mean V 100 were both non-significantly larger for SSCP based post-plans compared to DSCP based post plans (P = 0.76 and P = 0.68). ANOVA showed significant impact of prostate volume on the post-plan D 90 and V 100 . Conclusions : The advantages of the dual sagittal crystal probe did not lead to more accurate online planning by investigating DVH-parameters. The only factor found to have influence on the DVH-parameters was the prostate volume.